H-NS is a repressor of major virulence gene loci in Vibrio parahaemolyticus - Sun, Fengjun; Zhang, Yiquan; Qiu, Yefeng; Yang, Huiying; Yang, Wenhui; Yin, Zhe; Wang, Jie; Yang, Ruifu; Xia, Peiyuan; Zhou, Dongsheng (Frontiers in Microbiology, 2014)
Vibrio parahaemolyticus, a leading cause of seafood-associated diarrhea and gastroenteritis, harbors three major virulence gene loci T3SS1, Vp-PAI (T3SS1+tdh2) and T6SS2. As showing is this study, the nucleoid-associated DNA-binding regulator H-NS binds to multiple promoter-proximal regions in each of the above three loci to repress their transcription, and moreover H-NS inhibits the cytotoxicitiy, enterotoxicity, hemolytic activity, and mouse lethality of V. parahaemolyticus. H-NS appears to act as a major repressor of the virulence of this pathogen.